2021
DOI: 10.3390/antibiotics10080974
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Resazurin Cell Viability Assay to Monitor Escherichia coli and Salmonella Typhimurium Inactivation Mediated by Phages

Abstract: Bacterial inactivation using bacteriophages (or phages) has emerged as an effective solution for bacterial infections, but the screening methods used to evaluate the effectiveness of the phages to inactivate bacteria are not fast, reliable or precise enough. The efficiency of bacterial inactivation by phages has been evaluated by monitoring bacterial concentration either by counting colony-forming units (CFU), a laborious and time-consuming method, or by monitoring the optical density (OD), a less sensitive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The difference observed in the inhibition results shown in Figure 10 D(b,c), both addressing sessile bacteria, is due to the different degree of accuracy of the two methods. Resazurin assay accesses the metabolic activity of viable cells by fluorescence evaluation, providing reliable results of the bacterial viability [ 69 ]. However, CFUs counts, accounting for the bacteria that are able to form a colony, would prove both the cell viability and functionality, and is therefore the most accurate method [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference observed in the inhibition results shown in Figure 10 D(b,c), both addressing sessile bacteria, is due to the different degree of accuracy of the two methods. Resazurin assay accesses the metabolic activity of viable cells by fluorescence evaluation, providing reliable results of the bacterial viability [ 69 ]. However, CFUs counts, accounting for the bacteria that are able to form a colony, would prove both the cell viability and functionality, and is therefore the most accurate method [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In REMA, the nonfluorescent dye resazurin undergoes chemical reduction to red-fluorescent resorufin in metabolically active cells. 40 The obtained data showed that the cells treated at MBIC turn the blue color nonfluorescent resazurin into fluorescent red color resorufin using the natural reducing power of viable cells (see Figure S8 ). It is worth noting that the cells treated at MIC were unable to respirate and the resazurin remained blue.…”
Section: Effect Of Jccus On the Crab Biofilmmentioning
confidence: 89%
“…To confirm that the cells are viable at MBIC, a resazurin microtitre assay (REMA) plate was performed (see Figure S8). In REMA, the nonfluorescent dye resazurin undergoes chemical reduction to red-fluorescent resorufin in metabolically active cells . The obtained data showed that the cells treated at MBIC turn the blue color nonfluorescent resazurin into fluorescent red color resorufin using the natural reducing power of viable cells (see Figure S8).…”
Section: Effect Of Jccus On the Crab Biofilmmentioning
confidence: 90%
“…For the colourimetric bacterial cell viability determination, a resazurin dye (catalogue # RM125) assay was performed. The assay uses colourimetric redox dye, which changes the colour from blue (A 600 absorbance) in the oxidized form to pink colour when reduced (A 570 absorbance) due to the formation of resorufin [27] , [28] , [29] . For the assay, an equal volume of resazurin dye (67.5 mg/L) was mixed with treated bacterial suspension and incubated statically at 37 °C under dark for 4 h. After incubation, the samples were spectrophotometrically measured at 570 nm and 600 nm.…”
Section: Methodsmentioning
confidence: 99%